SEKILAS MENGENAI HUMAN COMMUNICATION (KOMUNIKASI INSANI ) VERBAL MAUPUN NONVERBAL Brief On Human Communication (Communication lnsani) Verbal Or Nonverbal - Kertopati, Ton (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
Communication     transaction:    basic   elements    and  factors,·        so  far    as   the communicator   concerned   all the  Communications    transactions   are  shaped   by some  important  influence  such as.The communicative  purpose   and knowledge  of the subject.The purpose   in communicating   is to attain  some goal  and the effectiveness with which  it is transmitted.Besides of  knowledge of  subject    matter   fundamental skills is important  regardless of  the situations in  which   a  communication    transaction    occurs verbal  or nonverbal communication   symbol.The ability  to use  our  voices  and  bodies  to express  ideas  orally  and  visually facilitates the understanding   and acceptance   basic  to successful functioning of communication  process.